Lutetium-177 labeled iPD-L1 as a novel immunomodulator for cancer-targeted radiotherapy - Myrna Luna-Gutiérrez; Erika Azorín-Vega; Rigoberto Oros-Pantoja; Blanca Ocampo-García; Pedro Cruz-Nova; Nallely Jiménez-Mancilla; Gerardo Bravo-Villegas; Clara Santos-Cuevas; Laura Meléndez-Alafort; Guillermina Ferro-Flores (EJNMMI Radiopharmacy and Chemistry, 2025)
Abstract Background Cancer immunotherapy is a relatively new approach to cancer treatment. Peptides that target specific pathways and cells involved in immunomodulation can potentially improve the efficacy of cancer therapy. Recently, we reported iPD-L1 as a novel inhibitor peptide that specifically targets the cancer cell ligand PD-L1 (programmed death ligand 1). PD-L1 is responsible for inhibiting the immune checkpoint protein PD-1 expressed by regulatory T cells. On the other hand, anti-PD-L1 immunotherapy in combination with external beam radiotherapy has shown improved outcomes in the treatment of breast and lung cancer. The aim of this research was to prepare 177Lu-labeled iPD-L1 and to preclinically evaluate its radiotherapeutic potential and role as a tumor immunomodulator by measuring macrophage activation, IL-10, TGFβ, and PD-L1 expression in 4T1 triple-negative breast cancer cells and murine 4T1 tumors after treatment with 177Lu-iPD-L1. Results The iPD-L1 ligand, characterized by UPLC mass, UV-Vis, and FT-IR spectroscopies, showed a chemical purity of 99%. The 177Lu-iPD-L1 radiochemical purity was 98.9 ± 1.1%. In vitro and in vivo studies demonstrated radiotracer stability in human serum (> 97% after 24 h evaluated by radio-HPLC), adequate affinity by the PDL1 protein (IC50 = 4.21 nM), and specific detection for PD-L1 assessed in 4T1, HCT116, and AR42J cancer cells, in which PD-L1 expression was verified by immunofluorescence and Western Blot assays. After treatment with 177Lu-iPD-L1 (0.4 Bq/cell), flow cytometry results showed a significant decrease in cell viability of 4T1 cells (dead 56.2%) compared to 177LuCl3 (dead 34.2%) and untreated cells (dead 9.4%). With high tumor uptake (6.97 ± 1.04%ID) and hepatobiliary and renal clearance, lutetium-177-labeled iPD-L1 delivered a tumor dose of 27 Gy/37 MBq and less than 0.36 Gy/37 MBq to non-source organs. PD-L1 positive tumors showed a significant increase in activated macrophages, PD-L1, IL-10, and TGFβ expression levels after 177Lu-iPD-L1 treatment as evaluated by ELISA assay and immunohistochemistry. Conclusions Therefore, this study warrants further dosimetric and clinical studies to determine the immunomodulatory effect and therapeutic efficacy of 177Lu-iPD-L1 in treating PD-L1-positive tumors in combination with anti-PD-1/PD-L1 immunotherapy protocols.